2019
DOI: 10.30621/jbachs.2019.652
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Properties and Clinical Use of the Turkish Version of the Functional Assessment of Cancer Therapy–Lung (FACT-L) Scale

Abstract: Objectives:psychometric properties of the Turkish version of the Functional Assessment of Cancer Therapy-Lung (FACT-L) scale and the sensitivity to changes in clinical indicators. Patients and Methods:This study was conducted within the framework of a national multicentre project. Patients with either stage IIIB or IV primary lung cancer diagnosed after April 2010were included in thisstudy. A classical confirmatory approach was used for both the reliability and validity analyses. Internal consistency was teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Cigarette smoking appears to be a risk factor that influences the quality of life of patients with lung cancer [20] in this study demonstrated that patients who smoked previously are three times more at risk for developing lung cancer than non-smokers and had significant impacts on quality of life. Patients with stage III lung cancer had significantly better physical well-being, higher social well-being, emotional status, well-improved-functioning status, and better ability to control Lung Cancer symptoms which agrees with a study done in Turkey when considering the stage of the tumor, the scale scores varied significantly in all dimensions among patients with stage III cancer [21] . In addition, the study done in China by [22] found that stage IV lung cancer patients had lower all domains of FACT-L scores than stage III patients.…”
Section: Methodssupporting
confidence: 90%
“…Cigarette smoking appears to be a risk factor that influences the quality of life of patients with lung cancer [20] in this study demonstrated that patients who smoked previously are three times more at risk for developing lung cancer than non-smokers and had significant impacts on quality of life. Patients with stage III lung cancer had significantly better physical well-being, higher social well-being, emotional status, well-improved-functioning status, and better ability to control Lung Cancer symptoms which agrees with a study done in Turkey when considering the stage of the tumor, the scale scores varied significantly in all dimensions among patients with stage III cancer [21] . In addition, the study done in China by [22] found that stage IV lung cancer patients had lower all domains of FACT-L scores than stage III patients.…”
Section: Methodssupporting
confidence: 90%